Improving quality of dried mangoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Drying mangoes in a way that keeps their flavour and texture is no easy task, but this is what researchers have done at the Inter-State School of Engineers and Rural Equipment (EIER) of Burkina Faso. When mangoes are treated with sulphur by burning...